Perceived importance of weight loss and exercise among endometrial cancer survivors with overweight or obesity: Implications for lifestyle modification interventions - Erin K. Tagai; Gina M. Mantia‐Smaldone; Andrew Belfiglio; Christina S. Chu; Emmanuel Lapitan; Heather Santos; Enrique Hernandez; David B. Sarwer; Suzanne M. Miller (Wiley, 2023)
Abstract Objective Type 1 endometrial cancer (EC) survivors who are overweight or obese are at increased risk of comorbidities and reduced quality of life. Lifestyle modification interventions (e.g., healthy eating, exercise) may help these women reduce excess weight and improve their quality of life. However, existing interventions have shown limited success. Guided by Self‐Determination Theory, the proposed study sought to identify factors associated with perceived importance of weight loss and exercise as well as interest in lifestyle modification interventions (components of extrinsic and intrinsic motivation) among EC survivors with overweight or obesity to inform future intervention development. Methods One hundred type 1 EC survivors [body mass index (BMI) ≥ 25 kg/m2] completed a cross‐sectional survey assessing sociodemographics, medical factors, exercise, risk perceptions and provider communication, quality of life, barriers to dieting and exercise, perceived importance of healthy lifestyles, and desired intervention content. Results EC survivors who were aware obesity is a risk factor for EC were significantly more likely to perceive weight loss as important and were interested in weight loss programs and receiving information about exercise (ps < 0.05). Additionally, EC survivors who reported their provider discussed the importance of a healthy weight after their diagnosis were significantly more likely to perceive exercise as important and were interested in receiving dieting information. Conclusions EC survivors expressed interest in lifestyle modification interventions. Increasing awareness about the risk of obesity and provider discussions about healthy weight during routine appointments may motivate EC survivors to engage in lifestyle modification interventions.